2008
DOI: 10.5194/acp-8-3369-2008
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance of the Brewer spectral UV measurements in Finland

Abstract: Abstract. The quality assurance of the two Brewer spectrophotometers of the Finnish Meteorological Institute is discussed in this paper. The complete data processing chain from raw signal to high quality spectra is presented. The quality assurance includes daily maintenance, laboratory characterizations, calculation of long-term spectral responsivity, data processing and quality assessment. The cosine correction of the measurements is based on a new method, and is included in the data processing software. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
76
0
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 42 publications
0
76
0
1
Order By: Relevance
“…More recent studies indicated that the measurements can be largely affected by the individual characteristics of each instrument (Gröbner et al, 2006) and that proper corrections are needed in order to keep the uncertainties within the above mentioned limits or even reduce them further (Garane et al, 2006;Karppinen et al, 2014;Lakkala et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies indicated that the measurements can be largely affected by the individual characteristics of each instrument (Gröbner et al, 2006) and that proper corrections are needed in order to keep the uncertainties within the above mentioned limits or even reduce them further (Garane et al, 2006;Karppinen et al, 2014;Lakkala et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Using the measurements of the Brewer, the irradiance scale is transfered to working standards, which are used for the calibration of the Brewer every 6 weeks. The procedure is described in more detail in Mäkelä et al (2016) and Lakkala et al (2008).…”
Section: Uv Spectroradiometer Calibrationsmentioning
confidence: 99%
“…The second Brewer is a double monochromator with a wavelength range from 290 to 365 nm. The Brewer time series is one of the longest homogenized time series measured in the Arctic (Lakkala et al, 2003(Lakkala et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature shows that the methods and algorithms differ amongst the stations maintaining spectrophotometers for measurements of solar spectral UV irradiance (Lam et al, 2002;Kazadzis et al, 2005;Garane et al, 2006, Lakkala et al, 2008Simic et al, 2008;Schneider et al, 2008;Ialongo et al, 2008;Sabburg et al, 2001;Damiani et al, 2012). The measurements with Brewer #037 and Brewer #107 spectrophotometers at Sodankylä and Jokioinen respectively have followed the WMO recommendations, with stability checks every 3-4 weeks and measurements of standard lamps in laboratory (darkroom) every 6-8 weeks.…”
Section: Introductionmentioning
confidence: 99%